On the measurement of trade-induced adjustment - Abdul Karim, Mohd Azhar; Elliott, Robert J. R. (Springer, 2003)
Globalisation and closer regional integration have led to significant increases in trade between nations that in turn impacts on existing long-standing trade partnerships. A consequence of changing trade patterns is an increase in the pressure for resources to reallocate between industries and sectors. This paper provides an integrated approach to the analysis of trade-induced adjustment that complements the existing literature. Adjustment pressures are documented in accordance with the theoretical underpinnings of the smooth adjustment hypothesis and satisfy a number of desirable criteria, monotonicity, consistency and country specificity. The applicability of the authors' approach is examined using UK manufacturing data.